Multi-level surgery for obstructive sleep apnea. Lingual tonsillectomy vs. hyoid suspension in combination with radiofrequency of the tongue base - Verse, Thomas; Wenzel, Stefan; Brus, Johannes (Sleep and breathing, 2015)
PurposeThe aim of this study was to compare results in patients with obstructive sleep apnea (OSA) undergoing multi-level surgery with two different surgical approaches to treat tongue base obstruction.Study designThis is a prospective, controlled clinical trial at a tertiary referral center.MethodsAltogether, 108 patients were separated into two groups according to the findings during drug-induced sleep endoscopy. Patients with enlarged lingual tonsils (N = 58; group A) underwent a lingual tonsillectomy (LT). Patients with small or absent lingual tonsils (N = 50; group B) underwent a hyoid suspension type 2 (HS) in combination with a radiofrequency treatment of the base of the tongue (RFT TB). In addition, all patients underwent an uvulopalatopharyngoplasty with tonsillectomy.ResultsAt baseline, there were no significant differences between the groups. In group A, the mean apnea hypopnea index (AHI) decreased by 49.7 %, and in group B by 48.3 %. Patients with simultaneous tonsillectomies showed significant better results as compared to patients after prior tonsillectomies (success rate 76.6 vs. 27.3 %). By comparing subgroups (with and without simultaneous tonsillectomy), patients in group A showed better results in terms of AHI reduction than patients in group B, indicating that LT may be superior to HS + RFT TB in treating OSA within our multi-level surgery concept.ConclusionSimultaneous tonsillectomy has a significant impact on objective results of multi-level surgery (MLS). Study results should be adjusted for this parameter. Having done this, MLS with LT seems to produce superior results as compared to HS + RFT TB. Nevertheless, our approach to treat patients differently according to their tongue base tonsil size did not substantially improve our surgical outcome as compared to a previous study.
Gesehen am 05.12.2018